2021
DOI: 10.1007/s00204-021-03063-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer drug resistance induced by EMT: novel therapeutic strategies

Abstract: Over the last decade, important clinical benefits have been achieved in cancer patients by using drug-targeting strategies. Nevertheless, drug resistance is still a major problem in most cancer therapies. Epithelial-mesenchymal plasticity (EMP) and tumour microenvironment have been described as limiting factors for effective treatment in many cancer types. Moreover, epithelial-to-mesenchymal transition (EMT) has also been associated with therapy resistance in many different preclinical models, although limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 238 publications
(286 reference statements)
1
61
0
Order By: Relevance
“…In line with our results, several studies have demonstrated that EMT is a key event in the development of chemoresistance in several tumors [ 39 , 54 , 55 ], including prostate [ 56 ] and bladder cancer [ 57 ]. In a previous study by our group, EMT was positively enriched in colorectal cancer cells with acquired resistance to oxaliplatin compared to their parental cell lines [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, several studies have demonstrated that EMT is a key event in the development of chemoresistance in several tumors [ 39 , 54 , 55 ], including prostate [ 56 ] and bladder cancer [ 57 ]. In a previous study by our group, EMT was positively enriched in colorectal cancer cells with acquired resistance to oxaliplatin compared to their parental cell lines [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Progress in treating metastatic disease is starting to take advantage of improved understanding of the interconnected signaling pathways that control EMT and stemness pathways during tumor progression. Since EMT is implicated in both cancer metastasis and induction of drug resistance, targeting EMT may have enormous therapeutic value [ 94 ]. As discussed above, many EMT drivers are epigenetically regulated, so drugs that influence DNA methylation, histone modification, and plasticity are emerging as potential therapeutic targets for overcoming EMT [ 95 ].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Cancer invasiveness has long been associated with increased drug resistance, yet little is known about the molecular mechanisms linking these two processes. Indeed, the highly conserved cellular process of EMT has emerged as a major contributor to therapy resistance by permitting polarized, immobile epithelial cells to transform into mesenchymal mobile cells due to loss of apico-basal polarity and cell–cell contacts [ 56 ].We observed strong repression of several mesenchymal genes in fusion-positive lines including SNAI1 (SNAIL) , SNAI2 (SLUG) , Vimentin (VIM) and TWIST . Interestingly, a bioinformatic-based analysis of the promoter regions of 16 ABC transporters by Saxena et al revealed binding sites for several EMT-inducing transcription factors including SNAI1 , SNAI2 , TWIST , E12 , E47 and FOXC2 , with TWIST , SNAI1 , and FOXC2 capable of increasing the promoter activity of ABC transporters [ 57 ].…”
Section: Discussionmentioning
confidence: 99%